(untitled) (Revista Archai, 2021)
The Socratic elenchos in Xenophon’s work plays a central role even though it may seem to have a secondary part. The following article aims to work on the xenophontic characterization of the Socratic elenchos, as well as his assessment from the point of view of its educational qualities. In this sense, the socratic elenchos potentialities will be analyzed in three directions: first, the strictly formative dimension; secondly, its role for acting in political affairs; and, finally, his contribution to the acquisition of the sophrosyne. Through this analysis I will explain why the portrait made by Xenophon of the Socratic elenchos should be understood as supplementary to the portraits made by others (like Plato) and not as an alternative to them.